Prevalence of asymptomatic bacteriuria among low risk pregnant women attending antenatal care clinic in tertiary hospital: a cross sectional study - Abbas, Ahmed M.; Kamel, Moustafa; Abdelrahman, Mohammed Z.; Youssef, Ahmed A.; Youssef, Mohammed A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The current study aims to identify the prevalence of asymptomatic bacteriuria among low-risk pregnant women attending the antenatal care clinic of tertiary University Hospital and to detect the most common causative organisms. Methods: A prospective cross-sectional study conducted at a tertiary University Hospital in the period between 1st November 2017 and 31st June 2018. All eligible women attending the outpatient clinic for antenatal care were approached to participate in the study. The recruited women were assessed through detailed history and clinical examination. Urine samples were taken for culture and sensitivity within two hours, in order to avoid bacterial multiplication. Urine culture and antibiotic sensitivity test were done. Results: The study included 250 women. The mean age of included women was 25.89±5.49 (18-42 years). The urine analysis results showed that 32% of cases had pus cells >5 per high power field and 10.4% of cases have protein (+). Casts were present in 0.8% of cases. RBCs >5 per high power field were present in 4.8% of cases. ASB is defined as urine culture with more than 100,000 colony forming unit; this was present in 30 cases. This indicates that the prevalence of ASB among studied cases was 12%. Enterococcus was the most prevalent organism as it was present in 36.7% among positive cases. Antibiotic sensitivity test was performed to the growing organisms indicated that teicoplanin, imipenem, cefoxitin, cefotaxime + clavulanic acid, Entrapenem, and trimethoprim + sulfamethoxazole are the most effective antibiotics against the most common organisms causing asymptomatic bacteriuria. Conclusions: The prevalence of asymptomatic bacteriuria among low-risk pregnant women is about 12%. Urine culture for asymptomatic bacteriuria should be the standard of care for evaluation of pregnant patient during antenatal care as regard presence or absence of UTI.